Socio-demographic factors and edentulism: the Nigerian experience - Akeredolu Patricia; Olusile Adeyemi; Esan Temitope; Esan Ayodeji (BMC, 2004)
Abstract Background The rate of total edentulism is said to be increasing in developing countries and this had been attributed mainly to the high prevalence of periodontal diseases and caries. Several reports have shown that non-disease factors such as attitude, behavior, dental attendance, characteristics of health care systems and socio-demographic factors play important roles in the aetiopathogenesis of edentulism. The aim of this study was to assess the relationship between socio-demographic factors and edentulism. Methods A total of 152 patients made up of 80 (52.6%) males and 72 (47.4%) females who presented in two prosthetic clinics located in an urban and a rural area were included in the study. The relationship between gender, age, socio-economic status and edentulism in this study population was established. Results No significant relationship between gender and denture demand was noted in the study. The demand for complete dentures increased with age while the demand for removable partial dentures also increased with age until the 3rd decade and then started to decline. A significant relationship was found between denture demand and the level of education with a higher demand in lower educational groups (p < 0.001). In addition, the lower socio-economic group had a higher demand more for prostheses than the higher group. Conclusions The findings in this study revealed a significant relationship between socio-demographic variables and edentulism with age, educational level and socio-economic status playing vital roles in edentulism and denture demand.